Sodium intake according to NOVA food classification in Brazil: trends from 2002 to 2018 - Eduardo Augusto Fernandes Nilson; Giovanna Calixto Andrade; Rafael Moreira Claro; Maria Laura da Costa Louzada; Renata Bertazzi Levy (Escola Nacional de Saúde Pública, Fundação Oswaldo Cruz, 2024)
Abstract: Excessive sodium intake is a major global public health issue and the identification of dietary sources and temporal trends in its consumption are a key to effective sodium reduction policies. This study aims to update estimates of sodium intake and its dietary sources in Brazil according to the NOVA food classification system. Records of 7-day food purchases of households from the Brazilian Household Budgets Survey of 2002-2003, 2008-2009, and 2017-2018 were converted into nutrients using food composition tables and the mean availability was estimated per 2,000kcal/day. Mean daily sodium available for consumption in Brazilian households has increased from 3.9 to 4.7g per 2,000kcal, from 2002-2003 to 2017-2018, over twice the recommended levels of sodium intake. From 2002-2003 to 2017-2018, the processed culinary ingredients, including table salt, represented the largest dietary source of sodium, although their participation in dietary sodium was reduced by 17% (66.6% to 55%), while the percentage of dietary sodium from processed foods increased by 20.3% and from ultra-processed foods increased by 47.6% (11.3% to 13.6% and 17% to 25.1%, respectively). In conclusion, the total household sodium availability remains high and has increased over time in Brazil, yet the participation of different dietary sources of sodium have gradually changed.